Heavy metals in the freshwater snail Indoplanorbis exustus - Abdul Manan Mat Jais (Universiti Putra Malaysia, 2015)
The freshwater snail Indoplanorbis exustus, locally known as siput kiki, was collected from three sampling stations, namely Ranau, Membakut and Kota Belud on the west coast of Sabah, Malaysia. These areas have rice fields, and are known to be exposed to pesticides and other agrochemicals. The snails contained 87.77+-0.80% water in flesh and 42.77+-0.01% in shell. Magnesium (4.31 mug/g), iron (28.0 mug/g) and nickel (1.5 mug/g) in the flesh were found to be higher than in the shell (Mg 2.26 mug/g, Fe 23.25 mug/g, Ni 0.75 mug/g). Manganese (21.4 mug/g), lead (13.5 mug/g) and calcium (313.40 mug/g) were higher in the shell than in the flesh (Mn 14.83 mug/g, Pb 4.00 mug/g, Ca 290.15 mug/g). Copper and zinc were evenly distributed in the flesh (0.12 mug/g, 6.75 mug/g) and shell (0.21 mug/g, 6.25 mug/g). The levels of the heavy metals in the flesh were still well below the levels toxic to human.